1989
DOI: 10.1128/iai.57.12.3735-3742.1989
|View full text |Cite
|
Sign up to set email alerts
|

Binding of staphylococci to mucus in vivo and in vitro

Abstract: The association of Staphylococcus aureus, Staphylococcus epidermidis, and Staphylococcus saprophyticus with tissues of the upper respiratory tract were compared by using an in vivo ferret model. Ferrets were challenged intranasally with a 1-ml volume of radiolabeled staphylococci (3 mg [dry weight]), were allowed to clear the bacteria in vivo for 90 min, and were sacrificed. Tissues from the right nasal fossa were harvested and processed for radioassay or histology. Of the recoverable staphylococci, .96% was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…Glycoproteins are highly glycosylated proteins (Verdugo 1990; Strous & Dekker 1992; Bansil, Stanley & LaMont 1995; Cone 1999; Perez‐Vilar & Hill 1999), where the protein core is usually not accessible to pathogens due to the carbohydrate side‐chains (Variyam & Hoskins 1983). Therefore, bacteria usually bind predominantly to the carbohydrate side‐chains of the glycoproteins (Sanford, Thomas & Ramsay 1989; Sajjan et al. 1992; Mantle & Husar 1993, 1994; Ascencio et al.…”
Section: Discussionmentioning
confidence: 99%
“…Glycoproteins are highly glycosylated proteins (Verdugo 1990; Strous & Dekker 1992; Bansil, Stanley & LaMont 1995; Cone 1999; Perez‐Vilar & Hill 1999), where the protein core is usually not accessible to pathogens due to the carbohydrate side‐chains (Variyam & Hoskins 1983). Therefore, bacteria usually bind predominantly to the carbohydrate side‐chains of the glycoproteins (Sanford, Thomas & Ramsay 1989; Sajjan et al. 1992; Mantle & Husar 1993, 1994; Ascencio et al.…”
Section: Discussionmentioning
confidence: 99%
“…Schwab et al (43) showed that S. aureus binding to airway epithelium, including nasal cells (ciliated and squamous), was sensitive to protease treatment of the bacteria. Sanford et al (41) studied S. aureus nasal colonization in a ferret model and found minimal adherence to respiratory epithelial cells but avid binding to the overlying mucus layer. A specific interaction of S. aureus with crude ferret mucus, as well as commercially available bovine submaxillary mucin, was demonstrated previously (41).…”
Section: Discussionmentioning
confidence: 99%
“…Sanford et al (41) studied S. aureus nasal colonization in a ferret model and found minimal adherence to respiratory epithelial cells but avid binding to the overlying mucus layer. A specific interaction of S. aureus with crude ferret mucus, as well as commercially available bovine submaxillary mucin, was demonstrated previously (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Host proteins do not enhance adherence of coagulase-negative staphylococci to biomaterials.Coagulase-negative staphylococci (CoNS) have become major nosocomial pathogens because of their capacity to colonize plastic biomaterials used in catheters and prosthetic devices (7). Several mechanisms have been proposed to explain this adherence to biomaterials, but the problem is far from solved (6,10,18,20). Recent studies suggest that host proteins coated onto biomaterials promote adherence of CoNS (10, 21).We have proposed that the capsular polysaccharide/adhesin (PS/A) mediates the initial adherence of CoNS to plastic biomaterials.…”
mentioning
confidence: 99%